2017
DOI: 10.1007/jhep11(2017)194
|View full text |Cite
|
Sign up to set email alerts
|

Digging deeper for new physics in the LHC data

Abstract: In this paper, we describe a novel, model-independent technique of "rectangular aggregations" for mining the LHC data for hints of new physics. A typical (CMS) search now has hundreds of signal regions, which can obscure potentially interesting anomalies. Applying our technique to the two CMS jets+MET SUSY searches, we identify a set of previously overlooked ∼ 3σ excesses. Among these, four excesses survive tests of inter-and intra-search compatibility, and two are especially interesting: they are largely over… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…We dubbed this the "monojet excess" because it is characterized by low jet multiplicity, no b-jets, and low / E T and H T . We found that the anomaly's kinematic distributions could not be well-fit by supersymmetry-like pair production of colored particles, or in simplified models for dark matter pair production [1]. Instead, a good fit was obtained using a colored scalar φ, resonantly produced through couplings to quarks, and decaying to an invisible massive Dirac fermion ψ and a Standard Model quark (the "mono-φ" model), see Fig.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…We dubbed this the "monojet excess" because it is characterized by low jet multiplicity, no b-jets, and low / E T and H T . We found that the anomaly's kinematic distributions could not be well-fit by supersymmetry-like pair production of colored particles, or in simplified models for dark matter pair production [1]. Instead, a good fit was obtained using a colored scalar φ, resonantly produced through couplings to quarks, and decaying to an invisible massive Dirac fermion ψ and a Standard Model quark (the "mono-φ" model), see Fig.…”
mentioning
confidence: 94%
“…1.To avoid decays of the ψ back to visible states, its Dirac partner ψ can be coupled to invisible states N andÑ . The interaction Lagrangian for the minimal model is [1] −L ⊇ gφ * q c i ψ+λφq c i q c j +m ψ ψψ +m 2 φ |φ| 2 +g ψ NÑ +h.c.(1) Here, the q i are the right-handed quarks. The scalar φ is a color-triplet, and its charge can be + 2 3 or − 1 3 .…”
mentioning
confidence: 99%
See 3 more Smart Citations